Facilitation of drug-resistant epilepsy and catastrophic status epilepticus in children with combined pituitary hormone deficiency. (July 2021) - Schönberger, Jan; Eckenweiler, Matthias; Klotz, Kerstin Alexandra; Sag, Yusuf; Shah, Mukesch; Fuchs, Hans; Kirschner, Janbernd; Jacobs, Julia
Abstract: Purpose: Clinicians and researchers often focus on the primary cause of seizures and epilepsy, but outcomes in individual patients also depend on multiple other variables, which might be easy to adjust. Previous studies suggest mutual interactions between endocrine disorders and epilepsy. We therefore hypothesized that combined pituitary hormone deficiency (CPHD) facilitates seizures and epilepsy. Methods: This is a retrospective study from a pediatric center. We determined the proportion of CPHD patients with epilepsy and examined basic clinical features in this group. Patients with super-refractory status epilepticus (SRSE) were reviewed to identify subjects with co-morbid CPHD. Those cases were analyzed in detail. Results: 12 of 73 CPHD patients (16%) also had epilepsy. Various etiologies of CPHD were represented, though five subjects had a cranial tumor or cortical malformation. Epilepsy was drug resistant in all but one patient. Among 12 identified patients with SRSE, 4 were unexpected new-onset cases. Three of these subjects also had CPHD with ACTH deficiency and a febrile infection prior to SRSE. Another common feature was the devastating clinical course: In all three patients, initial MRI already suggested severe neuronal damage, SRSE persisted for at least one week with ongoing need for anesthetic coma, and outcome was poor (two patients survived with major sequelae, one child deceased during the episode). Conclusion: Our findings indicate that CPHD may predispose for drug-resistant epilepsy and refractory seizures with catastrophic outcome. We suggest that in children with new-onset SRSE, screening for CPHD should be considered. Highlights: Epilepsy is frequent and severe in pediatric patients with CPHD. CPDH was frequent in children with new-onset SRSE. In these subjects, SRSE was particularly severe, and outcome catastrophic. CPHD may facilitate epilepsy and catastrophic status epilepticus in children.